Defining food literacy and dietary patterns among senior high school students in Malang City, East Java - Ira Dwijayanti; Yi Wen Chien; Ghislain G Poda; Jane C J Chao (Jurnal Gizi Indonesia (The Indonesian Journal of Nutrition), 2021)
Background: Food literacy is a collection of interrelated knowledge, skills, and behavior required to plan, manage, select, prepare, and eat food for further meeting dietary requirements and determining dietary intake. In Indonesia, 93.6% of all adolescents aged 10 years or over consumed an inadequate amount of fruits and vegetables and more than half often consumed food rich in sugar, fat and salt. Only one-third of students always had breakfast, only 3,81% always brought their own food to school. Adolescence has been considered as a nutritionally critical period of life. Improve the health promotion is important to prevent malnutrition and risk of chronic disease.Objectives: The study aimed to investigate the association of food literacy and dietary patterns among senior high school students in Malang, East Java.Materials and Methods: The cross-sectional study determined food literacy level and dietary patterns among senior high school students using a questionnaire as the instrument. This study recruited 464 students aged from 14 to 18 years old. Demographic characteristics of adolescents and their parents, adolescent food literacy, and dietary intake data were self-report collected. The height was measured using stature meter and weight using electronic scale to determine the BMI-for-age. The research was conducted from July to September 2015 in Malang, East Java.Results: Out of 464 adolescents, 59.9% were females, and female adolescents had a better food literacy (P < .001) and higher dietary pattern scores (P < .05). Adolescents whose family had higher income or higher percentage of income spent on food consumed more vegetables (P < .05) and dairy products (P < .05), and had higher dietary pattern scores (P < .05) compared with those whose family had lower income or lower percentage of income spent on food. The perception of food literacy (r = 0.187, P < .001), the behavior of food literacy (r = 0.333, P < .001), and overall food literacy (r = 0.329, P < .001) were positively correlated with dietary pattern scores.Conclusions: Food literacy is positively associated with dietary patterns in adolescents. Nutrition education is suggested to implement as a guide in healthy food choices for adolescent.